Analysis of the Effects of the Housing Foundation Activities on Economic and Environmental Development of Rural Settlements: A Case Study of Moghan (Germi) County Villages - Kalansara, Firouz Mahdizadeh; Jahani, Mahdi; Ahmadian, Mohammad Ali (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2022)
The Islamic Revolution Housing Foundation was established as the first executive body of the country in 1979 with the aim of helping the construction of housing for the deprived. Later, conductive (Hadi) plan preparation, conductive plan execution and the issuance of ownership document were added to the duties of the Foundation. Case studies are needed in order to understand the quality of the topics and the results of preparation and implementation of these plans. Accordingly, in this research, conductive plans, rural housing plans and eligible rural ownership documents in Moghan (Germi) County villages have been addressed. These plans have been implemented in 55 villages of the county. Thus, in the present study, we have investigated the effects of the Housing Foundation activities on economic and environmental development of Germi County villages. Here, a descriptive-analytical method based on documentary studies and field operations (questionnaire, interview, etc.) has been employed. Given the number of villages and the high number of households living in the villages, a sample size of 287 households was determined using Cochran formula and was distributed among the households in each village based on a systematic random sampling method. The research result based on the correlation coefficient test demonstrates that there is no significant relationship between the Housing Foundation activities and economic development of villages (p-value> 0.05). Therefore, the research hypothesis is rejected at a 95% confidence level. Further, the relationship between the Housing Foundation activities and environmental development of villages is not significant (p-value> 0.05). Hence, the hypothesis is rejected at a 95% confidence level.